Examining tournament theory in academe: implications for the field of human resource development. (1st January 2013) - Azevedo, Ross E.; Akdere, Mesut; Larson, Eric C.
In a unique approach to applying theory to practice based on concepts of participant observation, this paper discusses and analyses potential applications of tournament theory to the academe with specific implications to the field of human resource development (HRD). For purposes of this paper, tournament theory, originally intended to explain large compensation packages given to CEOs and other executives, provides analysis and predictions for academe and specifically to the field of HRD, where predictions are not very optimistic for those entering the field as academics. The paper argues that tournaments in academe are becoming more complex and more difficult to compete and win, thus making it much more difficult to advance in the academe.